Electrically tunable photo-aligned two-dimensional liquid crystal polarisation grating. Issue 8 (21st June 2019) - Li, Song-zhen; Zhao, Zhi-Wei; Wang, Cheng-Miao; Wang, Qi-dong; Yao, Lishuang; Peng, Zeng-Hui; Liu, Yong-gang; Xuan, Li
ABSTRACT: Two-dimensional liquid crystal polarisation grating based on twist liquid crystal has been demonstrated and fabricated by polarisation holography in this paper. The maximal diffraction efficiency of the second order is up to 90%. And the two-dimensional liquid crystal polarisation grating has the properties of electrically tenability and polarisation tenability. The two-dimensional polarisation grating diffracts light into a spot array. Different direction diffraction light is with different polarisation states. The intensity of the different orders diffraction light is optically controlled. Graphical Abstract: